MANAJEMEN PENGENDALIAN DAN KEPEMIMPINAN PEREMPUAN - Norma Mugi Lestari; Agus Budiharto (P3M STISIPOL Dharma Wacana Metro, 2018)
One of the positive effects of special attention to women is the expanding sector of women's activity into politics. This paper intends to describe management control and women's leadership in the People's Welfare Sector Trimurjo District Office, Central Lampung Regency. Using a descriptive qualitative research approach, this study concludes that female leaders already have standards or targets and targets that must be achieved in carrying out management functions by conducting meetings so that subordinates know what targets to be achieved.